Good-by Learning Journal: Strengthening Metacognitive Skills in OIDDE Learning Model - Hudha, Atok Miftachul; Handayani, Ning Rahayu; Setyawan, Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Students' metacognitive skills need to be empowered by learning to think at higher levels. This study aimed to analyze the effect of the application of learning journals in the OIDDE learning model on students' metacognitive skills. The type of research used is quasi-experimental. This type of research is quasi-experimental with a quantitative approach. Sampling used non-probability sampling with control and experimental classes involving 58 students. Data collection uses non-test, observation, and documentation test techniques. The results of learning data were analyzed using a one-way ANCOVA test. Metacognitive data skills were analyzed descriptively. The results showed that the students' metacognitive skills in the experimental class showed a level of planning skills of 42%, monitoring of 56%, and evaluation of 56%. Therefore, it is necessary to learn to organize learning, be aware of different types of thinking possibilities, and think in their own learning.